Committee of Safety and Protection (King's District, Albany County, N.Y.) record book - Committee of Safety and Protection (King's District, Albany County, N.Y.)
Manuscript record book of the Committee of Safety and Protection, King's District, Albany County, N.Y., dating 1776 May 28-1778 April 20. Subjects include raising revolutionary forces, procurement of military supplies, provision of civil government, public health, price controls, loyalists and loyalist property, and patriotism.
Committee formed by local citizens during the American Revolution to provide King's District, Albany County, N.Y., with a governing body between the collapse of British rule and the formal establishment of legitimate state, county, and town governments.
Collection material in English.
Keywords: United States. -- Continental Army; United States. -- Continental Army -- Supplies and stores; American loyalists -- New York (State) -- Albany County; Patriotism -- New York (State) -- Albany County; Price regulation -- New York (State) -- Albany County; Public health -- New York (State) -- Albany County; Albany County (N.Y.) -- History -- Revolution, 1775-1783.; New York (State) -- History -- Revolution, 1775-1783.; New York (State) -- Politics and government -- 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Committees of safety; United States -- History -- Revolution, 1775-1783 -- Confiscations and contributions